Performance assessment of multi-input-single-output (MISO) production process using transfer function and fuzzy logic: A case study of soap production. Issue 1 (31st December 2016) - Nwobi-Okoye, Chidozie Chukwuemeka; Okiy, Stanley
Abstract: In this research an improved and novel method of assessing the performance of multi input single output (MISO) processes, as typified by soap production process was studied. The method involves the combination of transfer function and fuzzy logic and was used in assessing the three years performance of a soap factory. A comparison of the years studied shows that the year 2011 with a performance rating λ of 0.761 which corresponds to the linguistic variable "Good" recorded the best performance, while the year 2012 with a performance rating λ of 0.250 which corresponds to the linguistic variable "Poor" recorded the worst performance. The result of this study will help to improve maintenance effectiveness, quality, utilization of raw materials and efficiency of MISO production processes.